2021
DOI: 10.3389/fbioe.2021.632029
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Cells Anchoring to Electrospun Hybrid Scaffolds With PHBV and HA Particles for Bone Tissue Regeneration

Abstract: Hybrid materials combining organic and inorganic compounds used as scaffolds are highly beneficial in bone regeneration. In this study, we successfully produced by blend electrospinning poly(3-hydroxybutyric acid-co-3-hydrovaleric acid) (PHBV) scaffolds enriched with hydroxyapatite (HA) particles to biomimic bone tissue for improved and faster regeneration processes. The morphology, fiber diameters, and composition of the scaffolds were investigated by scanning electron microscopy (SEM) techniques followed by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 51 publications
0
18
0
Order By: Relevance
“…The EDS spectrum of SBF immersed PHBV/MBGN/CIN20 microspheres confirmed the presence of Ca and P [ 82 ]. The peak of C corresponds to the polymeric matrix (PHBV) [ 69 , 83 ]. These results confirm the bioactivity of MBGN incorporated in PHBV/MBGN/CIN20 microspheres.…”
Section: Resultsmentioning
confidence: 99%
“…The EDS spectrum of SBF immersed PHBV/MBGN/CIN20 microspheres confirmed the presence of Ca and P [ 82 ]. The peak of C corresponds to the polymeric matrix (PHBV) [ 69 , 83 ]. These results confirm the bioactivity of MBGN incorporated in PHBV/MBGN/CIN20 microspheres.…”
Section: Resultsmentioning
confidence: 99%
“…Copyright 2020 Elsevier. Panels E and F reproduced with permission from ref ( 166 ). Copyright 2021 Karbowniczek, Kaniuk, Berniak, Gruszczyński, and Stachewicz.…”
Section: Biomedical Application Of Phbv Electrospun Fibersmentioning
confidence: 99%
“…The fibrous PHBV scaffolds enriched with inorganic HA particles were seen to support the anchoring and attachment of osteoblasts (see Figure 7 E,F). 166 It has been shown that the inclusion of HA particles in the fiber structure increases cell proliferation. These studies confirmed that the combination of organic and inorganic materials produces a hybrid material, the properties of which can support bone regeneration.…”
Section: Biomedical Application Of Phbv Electrospun Fibersmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of transmission electron microscopy have demonstrated that the authors managed to obtain ultrafine fibers with average diameter of approximately 200 nm and uniform distribution of HAP-based clusters ( Figure 2 ). In [ 78 ], the authors used blend electrospinning to produce poly(3-hydroxybutyric acid-co-3-hydrovaleric acid) (PHBV) filled with HAP particles. The composition and structural characteristics, including fiber diameter and surface morphology, were observed by means of scanning electron microscopy (SEM) supported by focused ion beam (FIB) application to confirm the presence of HAP inclusions and its integration with polymer matrix.…”
Section: Modern Polymer-based Fibrous Compositesmentioning
confidence: 99%